A novel 1p13.2 deletion associates with neurodevelopmental disorders in a three-generation pedigree - Lihua Yu; Hongke Ding; Min Liu; Ling Liu; Qi Zhang; Jian Lu; Fangfang Guo; Yan Zhang (BMC, 2023)
Abstract Background A multitude of studies have highlighted that copy number variants (CNVs) are associated with neurodevelopmental disorders (NDDs) characterized by a wide range of clinical characteristics. Benefiting from CNV calling from WES data, WES has emerged as a more powerful and cost-effective molecular diagnostic tool, which has been widely used for the diagnosis of genetic diseases, especially NDDs. To our knowledge, isolated deletions on chromosome 1p13.2 are rare. To date, only a few patients were reported with 1p13.2 deletions and most of them were sporadic. Besides, the correlation between 1p13.2 deletions and NDDs remained unclear. Case presentation Here, we first reported five members in a three-generation Chinese family who presented with NDDs and carried a novel 1.41 Mb heterozygous 1p13.2 deletion with precise breakpoints. The diagnostic deletion contained 12 protein-coding genes and was observed to segregate with NDDs among the members of our reported family. Whether those genes contribute to the patient's phenotypes is still inconclusive. Conclusions We hypothesized that the NDD phenotype of our patients was caused by the diagnostic 1p13.2 deletion. However, further in-depth functional experiments are still needed to establish a 1p13.2 deletion-NDDs relationship. Our study might supplement the spectrum of 1p13.2 deletion-NDDs.